Aging kinetics in the Cu-8 wt.% Al alloy with Ag additions - Adorno, A. T.; Guerreiro, M. R.; Silva, RAG (Elsevier B.V., 2003)
The influence of additions of 2, 4, 6, 8, 10 and 12 wt.% Ag in the isothermal aging kinetics of the Cu-8 wt.% Al alloy was studied using microhardness measurements, differential scanning calorimetry, optical and scanning electron microscopy and X-ray diffractometry. The results indicate that the presence of silver is responsible for the shift of the equilibrium concentration to higher Al contents, allowing the formation of the gamma(1) phase (Al4Cu9) in this alloy. For Ag additions up to 6% the dominant kinetic process is Ag precipitation and for additions from 8 to 12% Ag the nucleation of the perlitic phase dominates. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: alloys; precipitation; microstructure; mechanical properties; X-ray diffraction